Intrafraction monitoring of prostate motion during radiotherapy using the Clarity® Autoscan Transperineal Ultrasound (TPUS) system. Issue 4 (November 2017) - Richardson, A.K.; Jacobs, P.
Abstract: Introduction: Implementation of the Clarity ® Autoscan (Elekta) Transperineal Ultrasound (TPUS) system in Bristol is the first of its kind in the UK and we have already shown its utility in interfractional Image Guided Radiotherapy (IGRT). 14 This study establishes the extent of intrafraction prostate motion as measured by Clarity and explores the potential benefits of TPUS for intrafraction monitoring. Methods: Monitoring data was analysed for 526 fractions from 20 localised prostate cancer patients. Intrafraction prostate displacements exceeding thresholds of 3 mm, 7 mm and 10 mm along patient axes were assessed for frequency and duration of motion. Results: Prostate motion exceeds the above displacement thresholds during 52%, 8%, and 2% of fractions analysed. Displacement at the 3 mm threshold occurred for 100% of patients, 60% at 7 mm and 35% at 10 mm. The mean frequency and duration of displacements is low for the overall population. In contrast specific patients exhibit much higher displacement values. Posterior motion is most common, averaging at 24% of the treatment time at 3 mm, 3% at 7 mm and 1% at 10 mm, ranging up to 92%, 35% and 10% for individual patients. Conclusions: Intrafraction monitoring with Clarity has the potential to improve accuracy through application of in-treatment motion correction. This is most beneficial for specific patients who exhibit a higher frequency and/or duration of prostate motion. Consideration must be given to the added time implications and radiographer workload in clinical practice to correct for prostate motion. Clarity could help facilitate future protocols using tighter treatment margins, although further research is required. Highlights: This is the 1st clinical study performed with Clarity TPUS in the UK. We aimed to establish the extent of intrafraction prostate motion. Frequency and duration of motion varies considerably between individuals. Posterior motion is most common. In-treatment motion correction with Clarity appears worthwhile.